THE ROLE OF THE INDEPENDENT COMMISSIONER IN MODERATING CEO POWER ON COMPANY PERFORMANCE - Yolanda Pratami; Loveana Syaifora; Agustin Basriani; Mai Yuliza (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Business competition between companies requires companies to be able to survive by improving company performance. However, this has not been noticed by several banking companies listed on the Indonesia Stock Exchange which shows that the dominant company's performance has decreased from 2017 to 2019. The increase in company performance is inseparable from the ownership structure owned by parties with an interest in the company such as CEO power. and the role of independent commissioners. The purpose of this study was to obtain empirical evidence that CEO power has an effect on company performance and independent commissioners can moderate the relationship between CEO power and company performance. This study uses quantitative methods with multiple regression analysis while the population of this study are all banking companies listed on the Indonesia Stock Exchange from 2017 to 2019. The results of this study indicate that CEO Power has no effect on financial performance. Furthermore, independent commissioners do not have a moderating effect on the relationship between CEO Power and company performance Keywords: Company Performance, CEO Power, Commissioner